2019
DOI: 10.1093/dote/doz047.110
|View full text |Cite
|
Sign up to set email alerts
|

DOZ047.110: Recurrent tracheoesophageal fistula tracheoscopic chemocauterization with trichloroacetic acid

Abstract: Objective The aim of this study was to report the experience of two centers in the treatment of recurrent tracheoesophageal fistula (RTEF), by tracheoscopic chemocauterization with trichloroacetic acid (TCA). A surgical approach to RTEF has high morbidity and mortality. Some endoscopic techniques have been developed but nevertheless, optimal treatment is still not determined because of the low number of patients, short term of follow-up, and different techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
3
1
3
Order By: Relevance
“…We believe the optimal mean time between procedures should be one month, which is enough for healing and fibrosis formation at the chemically cauterized site, consistent with Sung's findings. Our results report greater effectiveness than Sung and Lara's (6,12) . It should also be mentioned that none of our patients had complications, and all procedures were managed on an outpatient basis, contrarily to what the aforementioned authors had previously described.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…We believe the optimal mean time between procedures should be one month, which is enough for healing and fibrosis formation at the chemically cauterized site, consistent with Sung's findings. Our results report greater effectiveness than Sung and Lara's (6,12) . It should also be mentioned that none of our patients had complications, and all procedures were managed on an outpatient basis, contrarily to what the aforementioned authors had previously described.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the endoscopic techniques combined have higher success rates (13) . Case publications by Sung in 2008 (11) , Lelonge in 2015 (6) , and Lara in 2019 (12) have reported better results with the endoscopic application of 50% topical trichloroacetic acid. Trichloroacetic acid is a strong acid used in chemical skin exfoliation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides de-epithelialization and fibrosis and leads to closure of the fistula (Figure 2A,B). Singhal et al reported successful chemocauterization with TCA in management of tracheoesophageal fistula for the (33) reported 100% success rate in three patients, 100% success rate in 14 patients (12 recurrent TEF and 2 H type TEF) and 83.3% success rate in 12 patients using TCA alone, respectively. Another point is that minimal morbidity is reported in these small series.…”
Section: B Amentioning
confidence: 99%
“…Gdanietz y Krause describieron con éxito el primer tratamiento de la fístula traqueoesofágica recurrente, con adhesivos plásticos mediante abordaje endoscópico en 1975 (10) ; en la última década, existe una variedad de técnicas endoscópicas que pueden ser empleadas de manera segura pero aun con bajo porcentaje de éxito. La aplicación de ácido tricloroacético ha sido descrita por Sung en 2008 (11) , Lelonge en 2015 (6) y Lara en 2019 (12) , donde reportan buenos resultados mediante la aplicación de ácido tricloroacético al 50% en forma tópica para cierre de fístula traqueoesofágica recurrente; sin embargo, su uso y seguimiento postoperatorio aún no se encuentra estandarizado. Hasta la fecha, ningún procedimiento endoscópico ha sido aceptado como el estándar de oro debido a los resultados variables y al pequeño número de casos reportados.…”
Section: Introductionunclassified